2016
DOI: 10.1002/ghg.1583
|View full text |Cite
|
Sign up to set email alerts
|

Integrated simulations of CO2 spreading and pressure response in the multilayer saline aquifer of South Scania Site, Sweden

Abstract: An integrated modeling approach/workflow, in which a series of mathematical models of different levels of complexity are applied to evaluate the geological storage capacity of the Scania Site, southwest Sweden, is presented. The storage formation at the site is a layered formation limited by bounding fault zones, and injection is assumed to take place from one existing deep borehole into all layers. A semi‐analytical model for two‐phase flow is first used to evaluate the pressure response and related parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Figure 6b shows the areal sweep with combined CO 2 (at the bottom) and water injection (at the top) due to which upward migration of the buoyant CO 2 was hindered along with reduction in CO 2 channeling resulting in enhanced dissolution of CO 2 in brine. The result can be correlated with the findings of Joodaki et al [34], which showed that CO 2 trapping is enhanced with CO 2 -brine co-injection. So, the mobile CO 2 concentration was the least.…”
Section: Evaluation Of Different Injection Schemessupporting
confidence: 89%
“…Figure 6b shows the areal sweep with combined CO 2 (at the bottom) and water injection (at the top) due to which upward migration of the buoyant CO 2 was hindered along with reduction in CO 2 channeling resulting in enhanced dissolution of CO 2 in brine. The result can be correlated with the findings of Joodaki et al [34], which showed that CO 2 trapping is enhanced with CO 2 -brine co-injection. So, the mobile CO 2 concentration was the least.…”
Section: Evaluation Of Different Injection Schemessupporting
confidence: 89%
“…Carefully conducted numerical simulations are critical for the understanding of the associated coupled physical and chemical processes (Pruess and García, 2002;Juanes et al, 2006;Doughty, 2007;Dai et al, 2016;Bacon et al, 2016;Xiao et al, 2016). An important additional complication arises from the geological heterogeneity of the target formation, such as stratigraphic architecture and facies distribution, which is difficult to estimate from the limited number of observations available (i.e., from the sparse networks of primarily vertical investigation wells) in a deterministic manner (Ambrose et al, 2007;Tsang et al, 2008;Gershenzon et al, 2015;Ritzi et al, 2016;Tian et al, 2016b;Ampomah et al, 2016). Therefore, robust and computationally effective methods for dealing with the uncertainty arising from the geological heterogeneity are in great need.…”
Section: Introductionmentioning
confidence: 99%